Humic Acid and Nitrogen Fertilizer Effects on Nitrogen Availability and Bacterial Population in Sipramin-Affected Paddy Soil - Melinda Trisya Yulianto; Wanti Mindari; Rossyda Priyadarshini; Dzarifah Zulperi; M. Ghufron Chakim (Acta Solum, 2026)
The accumulation of sodium (Na) due to the continuous use of sipramin reduces the physical, chemical, and biological quality of soil, thereby affecting nitrogen (N) availability and microbial activity. This study aimed to evaluate the combined effect of humic acid and different nitrogen fertilizer sources on nitrogen availability (NH₄+ and NO₃-) and bacterial population dynamics in sipramin-affected paddy soil. The experiment was conducted under greenhouse conditions using a completely randomized factorial design with two factors: humic acid doses (0, 20, 40, and 60 kg ha-¹) and nitrogen fertilizer sources (NPK Phonska, urea, KNO₃, and MAP) at an equivalent rate of 92 kg N ha-¹. Observations included NH₄+, NO₃-, and total bacterial populations, and data were analyzed using analysis of variance (ANOVA). The results showed that the interaction between humic acid and nitrogen fertilizer did not significantly affect nitrogen availability. However, both factors individually showed significant effects on NO₃- availability, indicating their role in influencing nitrogen dynamics. Bacterial populations increased from 7 to 21 Day After Treatment (DAT) and decreased at 42 DAT, reflecting temporal microbial dynamics during incubation. Although changes in bacterial populations coincided with variations in nitrogen forms, this relationship could not be directly confirmed due to the limitation of total culturable bacteria analysis. These findings highlight the importance of humic acid and nitrogen fertilizer management in regulating nitrogen dynamics under high-Na soil conditions, while further studies on specific microbial groups are needed to better understand the underlying mechanisms.